2016
DOI: 10.4155/bio-2016-0116
|View full text |Cite
|
Sign up to set email alerts
|

Relative Distribution of Gb 3 Isoforms/Analogs in Nod/Scid/Fabry Mice Tissues Determined by Tandem Mass Spectrometry

Abstract: Aim: Fabry disease is a lysosomal storage disorder leading to glycosphingolipid accumulation in different organs, tissues and biological fluids. The development of a Fabry disease gene therapy trial is underway in Canada. A tool to determine the distribution of Gb3 biomarkers in tissues of Fabry mice might be applicable to monitor the effect of gene therapy. Results & methodology: An ultra-performance LC–MS/MS (UPLC–MS/MS) method for the analysis of 22 Gb3 isoform/analogs in various Fabry mice tissues was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Mass spectrometry-based proteomics has been recognized as a powerful tool with a potential to uncover detailed changes in protein expression [29]. To date, most of the proteomics studies performed on FD patients examined FD-affected renal tissue or plasma; however, few studies of protein expression have used FD-affected human heart tissue [30,31]. Although it has been revealed that Gb3 accumulation induces endothelial KCa3.1 degradation in Gla -knockout mice through clathrin and Rab5C, which are the critical components of endosome maturation machinery [32], the proteomic profiling performed in our study revealed that GLA knockout led to the downregulation of Rab GTPases, including RAB11 subfamily, which are involved in recycling from an endosomal compartment to the plasma membrane, and was shown to contribute to exosome secretion in neuronal cells [33], although the molecular mechanism of RAB11 function in exosome secretion has yet to be deciphered, especially regarding its downstream effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry-based proteomics has been recognized as a powerful tool with a potential to uncover detailed changes in protein expression [29]. To date, most of the proteomics studies performed on FD patients examined FD-affected renal tissue or plasma; however, few studies of protein expression have used FD-affected human heart tissue [30,31]. Although it has been revealed that Gb3 accumulation induces endothelial KCa3.1 degradation in Gla -knockout mice through clathrin and Rab5C, which are the critical components of endosome maturation machinery [32], the proteomic profiling performed in our study revealed that GLA knockout led to the downregulation of Rab GTPases, including RAB11 subfamily, which are involved in recycling from an endosomal compartment to the plasma membrane, and was shown to contribute to exosome secretion in neuronal cells [33], although the molecular mechanism of RAB11 function in exosome secretion has yet to be deciphered, especially regarding its downstream effectors.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that constant digestion by SCDase occurred in both Gb3 isoforms and Gb3 analogs. The presence of Gb3 analogs containing lyso-Gb3 analogs has been suggested in Gla knockout mouse organs (28,29) and the plasma of patients with Fabry disease (19), but this is the first experimental data demonstrating the presence of Gb3 analogs in mouse organs. LC-MS/MS has been widely used to determine Gb3 content in the plasma of patients with Fabry disease (13) and in mouse organs (31,32), and it can detect selected Gb3 isoforms but not Gb3 analogs.…”
Section: Deacylation Of Gb3 From Different Organs Of Gla Tm Tg(cag-a4mentioning
confidence: 92%
“…Next, we assessed whether assaying Gb3 after SCDase deacylation was possible with heterogenous Gb3 containing various isoforms and analogs. As different Gb3 isoforms and analogs have been detected in different mouse organs (28,29), we purified Gb3 from the heart, kidneys, spleen, and liver from Gla tm Tg(CAG-A4GALT) mice. The total Gb3 purified from each organ was weighed, and 4 μg of each preparation was subjected to TLC and visualized with orcinol-sulfuric acid reagent, as previously described (30).…”
Section: Deacylation Of Gb3 From Different Organs Of Gla Tm Tg(cag-a4mentioning
confidence: 99%
“…The MS/MS method can also be used for research purposes to characterize different isoforms of the various SLs in various tissues and samples; indeed, their composition can be variable from one tissue to another (Sevin et al 2007, Provençal et al 2016. Methylated isoforms of Gb 3 are elevated in urine of patients affected with variant FD carrying the p.Asn215Ser mutation (Abaoui et al 2016).…”
Section: Sphingolipidsmentioning
confidence: 99%